Performance analysis routing protocol between RIPv2 and EIGRP with termination test on full mesh topology - D. R. Prehanto; A. D. Indriyanti; G. S. Permadi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Data access on a company is a very important part of an institution or a college. Especially in the present time, the internet has become an important thing in human life. With the existence of certain means there is a problem that will arise, needed solution or way out on a network that can be called protocol. Because an institution needs to choose network methods properly and safely.This study focuses on addressing the path/route of data packets to be sent will be governed by this routing protocol in the form of table routing. Routing used adip RIPv2 with EIGRP which will be compared on both routing protocol which is better against predetermined situation previous.The result of the research using CISCO Packet Tracer 7.10 software shows that EIGRP routing run on two topologies has faster convergence time speed with an average time of 0.01 - 0.02 seconds as well as the change of its routing table at once. Unlike RIPv2 routing that takes longer than EIGRP routing is with the time range from 0.01 to 0.19.